The diagnostic pitfalls of mucormycosis - Mauro, Margherita; Lo Cascio, Giuliana; Balter, Rita; Zaccaron, Ada; Bonetti, Elisa; Vitale, Virgina; Chinello, Matteo; De Bortoli, Massimiliano; Brazzarola, Paolo; Bruno, Costanza; et al. (Mediterranean Journal of Hematology and Infectious Diseases, 2020)
Background Invasive mucormycosis is a very aggressive fungal disease among immunocompromised pediatric patients caused by saprophytic fungi that belong to the order of the Mucorales. Case Report We describe a case of of Lichtheimia corymbifera infection in a 15-year-old child with B-cell Non-Hodgkin Lymphoma (NHL) involving lung, kidney and thyroid that initially was diagnosed as probable aspergillosis delaying the effective therapy for mucormycosis. Conclusions This case showed that also intensive chemotherapy with rituximab may represent a risk factor for mucormycosis infection. Liposomal amphotericin B and surgery remain key tools for a successful treatment of this aggressive disease.